Measurement and evaluation in human performance - Morrow, James R. Jr. 1947-; Mood, Dale; Zhu, Weimo 1955-; Kang, Minsoo (Physical education teacher)
"This book addresses the fundamentals of collecting and analyzing data of human performance and applying the results to real-life situations. Focusing on the core concepts of reliability and validity of data, the text provides tools for evidence-based decision making that can be applied to physical therapy, allied health professions, kinesiology, sport and exercise science, physical education, health, and fitness"
Concepts in tests and measurements -- Using technology in measurement and evaluation -- Descriptive statistics and data distribution -- Correlation and prediction -- Inferential statistics -- Reliability and validity -- Criterion-referenced test : cut scores, reliability and validity -- Evaluation : theory and practice -- Developing written tests and surveys -- Assessment of health-related physical fitness -- Assessment of performance-related fitness --Assessment of motor abilities, skills and performance -- Psychological measurements in sports and exercise -- Performance-based assessment : alternative ways to assess student learning.
MS Salazar (Recommending faculty) AY2022-2023
Includes bibliographical references and index.
Keywords: Physical Education and Training; Physical Fitness; Monitoring, Physiologic -- methods; Athletic Performance